Industrial evidence in the Development of Agglomerates from Agroindustrial Waste - Díaz Cañas, Edith Johanna
The Textile and Leather Manufacturing Centre, Capital District Regional, through the Research, Technological Development and Innovation System (SENNOVA), has intensified its efforts in the study of materials that mitigate the environmental impact generated by the textile industry’s production processes. The transformation of waste into new materials has become one of the central research axes for the fashion and clothing industry. From this point of view, agricultural residues are of great interest for the development of new materials, due to their characteristics of reusability and biodegradability; in the case of uchuva mats, aspects such as: protection of the fruit, degree of water repellency, degree of impermeability, ability to repel insects, among others, attract attention. The purpose of this project is to present some evidence in the field of the development of new materials from agribusiness waste, to publicize the potential of cape gooseberry mats as raw material in the generation of industrial valuable products.